(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This study aimed to evaluate the hemostatic derangement in patients undergoing elective cardiac surgery using cardiopulmonary bypass. Total 55 patients of either sex, were divided into three groups: Group A (n=20): Patients selected for elective cardiac surgery without cardiopulmonary bypass; Group B (n=20): Patients who undergone cardiac surgery with cardiopulmonary bypass time <90 min; and Group C (n=15): Patients who undergone cardiac surgery with cardiopulmonary bypass time either 90 min or more. The difference of mean hemoglobin, total count of WBC, and platelet count on immediate post-operative period and at 7 days after surgery were statistically significant among the groups. The mean hematocrit value, fibrinogen level and coagulation profile were statistically significant between the two groups in comparison to pre-operative value. The mean cross-clamp time and bypass time were statistically significant between the two sub-groups of cardiopulmonary bypass population. The mean blood loss was more (1513.3 ± 307.9 mL) where the cardiopulmonary bypass was used for >90 min in comparison to other population. Prolong cardiopulmonary bypass time associated with more hemostatic abnormalities and complications can be minimized by shortening the bypass time.